Critical Discourse Analysis of an ilocutive agent of the Novel The Help by Kathryn Stockett - Constantin Agramonte, Regina de las Mercedes (2020)
The black feminist ideology in literary discourse is the object of study of this research, which is aiming at determining how the discourse of an ilocutive agent reflects the change of ideology of Southern African-American women in the 1960s. Then, the characterization of the ilocutive agent as valuating subject is carried out. This research analyzes the novel The Help. Written by Kathryn Stockett, this novel describes the situation of African- American women in Mississippi during the Civil Rights Movement. An ilocutive agent of the novel was chosen to critically analyze her discourse. Theory involving discourse, Critical Discourse Analysis, black feminist ideology, and modality was presented in the research. The methodology included a literary review, the historical- logical, the inductive-deductive,  analytic-synthetic methods, a literary analysis and a Critical Discourse Analysis. The results have shown that the ilocutive agent has positive and assertive self-valuations as a  member of the community, whereas regarding her marriage the valuations are negative. The valuations are also negative and the ilocutive agent is gushing when she says her opinion on the context she is living.